Analisis Pengaruh Akad Salam (Pre-Order) dan Akad Wakalah (Cash On Delivery) Pada Marketplace Terhadap Perilaku Konsumen - Efrizal Novianto; Kartawan K; Mulia Amirullah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the analysis of the effect of Salam (Pre-Order) and Wakalah (Cash On Delivery) contracts on consumer behavior. This is interesting to be researched and studied more deeply about what are the reasons consumers buy a product on the marketplace. And the features available on the marketplace that aim to make it easier for people to buy a product. This research was conducted using a survey method by distributing questionnaires to the community of Kertasari sub-district, Ciamis district, Ciamis district, West Java. And analysis with multiple linear regression. This model emphasizes the influence of Salam (Pre-Order) and Wakalah (Cash On Delivery) contracts on consumer behavior whose analysis results are processed with IBM SPSS 25.0. The results showed that partially the Salam (Pre-Order) contract had an insignificant but insignificant effect on Consumer Behavior, the Wakalah (Cash On Delivery) contract had a significant effect on Consumer Behavior and simultaneously the Salam (Pre-Order) and Wakalah (Cash On Delivery) contract. ) has a significant effect on consumer behavior.